Epidemiology and global burden of headache and migraine - Ogunlaja, Oyindamola I. (Henry Stewart Talks, 2023)
Epidemiology and global burden of headache and migraine, Tension-type headache (TTH) and Migraines, Probable medication overuse headache (pMOH), Disability-adjusted life years (DALYs), Level 3 and 4 causes of global disability, Lost productive time due to headache disorders